PARENTING TEENAGER: VOLUME OF PROBLEM - Oksana Е. Kondratiuk; Natalya G. Kulikova (Открытое образование (Москва), 2016)
The problems of psychical new formations of teens are considered. The problem of analysis of reasons of instability of psyche of teenager is put in investigation of emotional changes in his subconsciousness, entering into a conflict with conscious options, desires and reasons. Connection of spiritual crisis of society with actuality of problem of socialization of teenager is shown.